Pengaruh Jumlah dan Rasio Sudut Lengkung Sudu Terhadap Unjuk Kerja Turbin Angin Savonius Heliks - Ahmad Lazim Rosyid; Ikhwanul Qiram; Dewi Sartika (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
The helical Savonius is a vertical wind turbine that can utilize wind energy to become a renewable energy source. This study aims to determine the effect of the number of blades and the ratio of blade bends on the performance of the Savonius helical wind turbine. The research was conducted through experimentation using variations in the number of blades 2 and 3 blades. Variation of blade bending ratio H / L = 6/10, 7/10 and 8/10 and variations in wind speed (4.0), (5.2), (6.4) and (7.4) m / s. The turbine performance analysis is reviewed based on the shaft rotation (RPM) of the turbine and the output voltage (volts) generated by the generator connected to the turbine shaft. The results showed that the wind speed, the number of blades, and the blending ratio of the blades affect the performance of the Savonius helical wind turbine. The results of the maximum wind turbine performance test at a variation of 3 blades, a ratio of 6/10, and a wind speed of 7.4 m / s, produce a shaft rotation value of 472.9 rpm and a generator output voltage value of 5.51 volts. Keywords: Helical Savonius, number and ratio blade bend, wind speed, performance